Issues in the Jewish Christian Dialogue: Jewish Perspectives on Covenant, Mission and Witness - Frizzell, Lawrence (Journal of Dharma, 1981)
Helga Croner and Leon Klenicki (Eds.) Issues in the Jewish Christian Dialogue: Jewish Perspectives on Covenant, Mission and Witness, Ramsey (N. J.) : Paulist Press 1979, pp. viii + 189, $7.95.